The role of Se content in improving anti-tumor activities and its potential mechanism for selenized Artemisia sphaerocephala polysaccharides. Issue 5 (4th February 2021) - Liu, Shuang; Hu, Jiahuan; Li, Min; Zhu, Shengyong; Guo, Shujuan; Guo, Hongyun; Wang, Tao; Zhang, Yongdong; Zhang, Ji; Wang, Junlong
Abstract : Potent Se content-dependent anti-tumor activities of selenized Artemisia sphaerocephala polysaccharides by inhibition of tumor cell growth, and induction of mitochondria and death receptor-mediated apoptosis. Abstract : Drawing an instructive point on the correlation between Se content and anti-tumor effects is helpful to develop Se-polysaccharides with potential anti-tumor activities. In this work, Se content-related anti-tumor activities are assessed in vitro by multiple comparisons among Na2 SeO3, Artemisia sphaerocephala polysaccharide (ASP), and selenized ASP (SeASPs, Se contents 4344–13 030 μg g −1 ) synthesized by a chemical modification method. The results suggest that SeASPs exhibit potent anti-proliferation activities against three kinds of tumor cells by inducing apoptosis and cell cycle arrest, which is positively correlated to Se content. Meanwhile, SeASPs display low cytotoxicity against normal cells as compared with Na2 SeO3 and 5-FU. A mitochondrial membrane potential assay and western blotting analysis suggest that the SeASPs induce HepG2 cell apoptosis via mitochondrial and death receptor pathways, which is confirmed by the reduced mitochondrial membrane potential, upregulated Bax/Bcl-2 ratio, promoted Cyt C release, and increased expression level of caspase-3/-9/-8. In an in vivo anti-tumor assay, SeASP with a high Se content (13 030 μg g −1 ) also obviously inhibits H22 tumor growth in a dose-dependent manner, and a tumor suppression rate of 45.10% is observed. In addition, the results of ELISA analysis suggest that SeASPs obviously increase the concentration of serum NO, cytokines (IL-1β, IL-6, TNF-α), and Ig-G in a dose-dependent manner as compared with the control and ASP group. It could be concluded that adjusting the Se content might be an effective approach to improve the anti-tumor activities of Se-polysaccharides.